Claustrum projections to prefrontal cortex in the capuchin monkey (Cebus apella) - Reser, David H.; Richardson, Karyn E.; Montibeller, Marina O.; Zhao, Sherry; Chan, Jonathan M. H.; Soares, Juliana G. M.; Chaplin, Tristan A.; Gattass, Ricardo; Rosa, Marcello G. P. (Frontiers in Systems Neuroscience, 2014)
We examined the pattern of retrograde tracer distribution in the claustrum following intracortical injections into the frontal pole (area 10), dorsal (area 9), and ventral lateral (area 12) regions of the rostral prefrontal cortex in the tufted capuchin monkey (Cebus apella). The resulting pattern of labeled cells was assessed in relation to the complex three-dimensional geometry of the claustrum, as well as recent reports of claustrum-prefrontal connections in other primates. Claustrum-prefrontal projections were extensive, and largely concentrated in the ventral half of the claustrum, especially in the rostral 2/3 of the nucleus. Our data are consistent with a topographic arrangement of claustrum-cortical connections in which prefrontal and association cortices receive connections largely from the rostral and medial claustrum. Comparative aspects of claustrum-prefrontal topography across primate species and the implications of claustrum connectivity for understanding of cortical functional networks are explored, and we hypothesize that the claustrum may play a role in controlling or switching between resting state and task-associated cortical networks.